The Role of Islamic Religious Education in Developing Student Character in the Digital Era: Peran Pendidikan Agama Islam Dalam Mengembangkan Karakter Mahasiswa Di Era Digital - Pinggala Wisnu Gali Wardhana, ingga; Nathan Andira Raditya (SALIHA: Jurnal Pendidikan Islam, 2025)
The role of Islamic religious education cannot be separated from developing student character in the current digital era, because with better and more focused religious education, student behavior becomes more educated and moral in accordance with religious teachings and does not deviate in their daily activities. This journal was created to discuss and explore more deeply the importance of Islamic religious education in developing students' character to be more ethical and behave in accordance with the teachings of the Islamic religion. The research background and further discussion in this journal are to help direct students to form characters with noble character who refer to norms in society, especially those originating from Islamic religious law in facing the challenges of rapidly developing technology in the digital era 4.0 towards 5.0. This. This journal was created with the aim of researching and reviewing further the role of Islamic religious education in higher education guided by lecturers, the academic community, especially at the Electronic Engineering Polytechnic Institute of Surabaya in educating, developing character and morals of students, both inside and outside the campus environment. This journal uses research with a qualitative approach with case study methods and data collection techniques carried out by in-depth interviews with peers within the Electronic Engineering Polytechnic Institute of Surabaya campus, field observations carried out in classrooms, and drawing conclusions.